2022
DOI: 10.21203/rs.3.rs-1430047/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient Tactile Encoding of Object Slippage

Abstract: Humans exhibit a remarkably robust reaction to external perturbations that prevent dropping objects held in hand, using only tactile inputs. In less than 200 ms, the sensorimotor system processes tactile information stemming from the deformation of the skin, to determine the frictional strength of the contact and to react accordingly. Given the thousands of afferents innervating the fingertips, it is unclear how the nervous system can process such a large influx of data in a sufficiently short time span. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that stick-to-slip events elicit strain waves on the surface of the fingertip skin (Delhaye et al, 2021 ;Willemet et al, 2022 ;du Bois de Dunilac et al, 2022 ), but their effects on the sub-surface structure are unclear. Additionally, reversing the plate's movement direction changes the tangential force applied to the skin and induces shear deformations within the tissue, but it is unclear whether these are absorbed in surface skin layers or in deeper tissues.…”
Section: Lateral Sliding and Stick-to-slipmentioning
confidence: 99%
“…Previous studies have shown that stick-to-slip events elicit strain waves on the surface of the fingertip skin (Delhaye et al, 2021 ;Willemet et al, 2022 ;du Bois de Dunilac et al, 2022 ), but their effects on the sub-surface structure are unclear. Additionally, reversing the plate's movement direction changes the tangential force applied to the skin and induces shear deformations within the tissue, but it is unclear whether these are absorbed in surface skin layers or in deeper tissues.…”
Section: Lateral Sliding and Stick-to-slipmentioning
confidence: 99%
“…Previous studies have shown that stick-to-slip events elicit strain waves on the surface of the fingertip skin (Delhaye et al, 2021 ;Willemet et al, 2022 ;du Bois de Dunilac et al, 2022 ), but their effects on the sub-surface structure are unclear. Additionally, reversing the plate's movement direction changes the tangential force applied to the skin and induces shear deformations within the tissue, but it is unclear whether these are absorbed in surface skin layers or in deeper tissues.…”
Section: Lateral Sliding and Stick-to-slipmentioning
confidence: 99%